The Effectiveness of Acupressure Therapy on Decreasing Complaints of Nausea and Vomiting in Pregnant Women - Dita Indah Sari; Sri Wahyuningsih (KHD-Production, 2021)
Nausea and vomiting or emesis gravidarum is a physiological complaint. Still, if this complaint of nausea and vomiting is not treated quickly, it will cause a pathological condition, namely hyperemesis gravidarum. So that every time you eat and drink, there are complaints of continuous vomiting, which will lead to malnutrition and dehydration in pregnant women. The thing that can be done to prevent these complications is a non-pharmacological therapy, namely acupressure. This literature review aims to determine the effectiveness of acupressure therapy in reducing complaints of nausea and vomiting in pregnant women. The method of this study is a literature review using data sources based on literature studies from the ScienceDirect, PubMed, and Scholar databases in the last 5 years. The strategy used to find articles using PICO. Keywords according to the topic of the literature review using Boolean (AND, OR, NOT). The results obtained 9 articles that were reviewed. It was found that acupressure therapy at point P6, point KID21, Zu San Li, and point Gong Sun effectively reduced complaints of nausea and vomiting in pregnant women who were carried out routinely. The conclusion from this literature review is that non-pharmacological acupressure therapy effectively reduces complaints of nausea and vomiting in pregnant women.